Thermochemical and bacterial sulfate reduction in the Cambrian and Lower Ordovician carbonates in the Tazhong Area, Tarim Basin, NW China: evidence from fluid inclusions, C, S, and Sr isotopic data. Issue 3 (29th September 2014) - Jia, L.; Cai, C.; Yang, H.; Li, H.; Wang, T.; Zhang, B.; Jiang, L.; Tao, X.
Abstract Petrographic features, C, O, S, and Sr isotopes were determined, and fluid inclusions (FI) were analyzed on various stages of vug‐ and fracture‐fillings from the Cambrian and Lower Ordovician reservoirs in the Tazhong area, Tarim basin, NW China. The aim was to assess the origin of pyrite and anhydrite and the processes affecting sulfur during diagenesis of the carbonates. Pyrite from seven wells has δ34S values from −22‰ to +31‰. The pyrites with low δ34S values from −21.8‰ to −12.3‰ were found close to fracture‐filling calcites with vapor‐liquid double‐phase aqueous fluid inclusions homogenization temperatures (FI‐Th) from 55.7 to 73.2°C, salinities from 1.4wt% to 6.59wt% NaCl equiv and δ13C values from −2.3‰ to −14.2‰, indicating an origin from bacterial sulfate reduction by organic matter. Other sulfides with heavier δ34S values may have formed by thermochemical sulfate reduction (TSR) during two episodes. The earlier TSR in the Middle and Lower Cambrian resulted in pyrites and H2S having δ34S values from 30 to 33‰, close to those of bedded anhydrite and oilfield water (approximately 34‰). The later TSR is represented by calcites with δ13C values as light as −17.7‰ and FI‐Th of about 120–145°C, and pyrite and H2S with δ34S values close to those of the Upper Cambrian burial‐diagenetic anhydrite (between +14.8‰ and +22.6‰). The values of the anhydrite are significantly lighter than contemporary seawater sulfates. This together with 87Sr/86Sr values of anhydrite and TSR calcites from 0.7091 to 0.7125 suggests a source from the underlying Ediacaran seawater sulfate and detrital Sr contribution.